Recent Advances in Transition-Metal-Free Late-Stage C-H and N-H Arylation of Heteroarenes Using Diaryliodonium Salts - Thierry Besson; Corinne Fruit (MDPI AG, 2021)
Transition-metal-free direct arylation of C-H or N-H bonds is one of the key emerging methodologies that is currently attracting tremendous attention. Diaryliodonium salts serve as a stepping stone on the way to alternative environmentally friendly and straightforward pathways for the construction of C-C and C-heteroatom bonds. In this review, we emphasize the recent synthetic advances of late-stage C(sp2)-N and C(sp2)-C(sp2) bond-forming reactions under metal-free conditions using diaryliodonium salts as arylating reagent and its applications to the synthesis of new arylated bioactive heterocyclic compounds.